(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Language as an international language becomes crucial nowadays, therefore the four English language skills must be taught as early as possible. English speaking skills is one of the most challenged abilities to be taught. Speaking skills is one of the most crucial language skills to be mastered. Picture series are used as a medium of teaching to encourage students’ self esteem in speaking English. The Toar Lumimuut story was used as to promote and preserve local wisdom that are contained. There are three stages in conducting this community service program namely preparation, teaching, dan evaluation. Students at SD Negeri 49 Manado are eager to learn English with pictures series as a medium of teaching. They are excited as seeing the pictures of Toar Lumimuut story that are being told using English. They were then asked to recounted the story using the same pictures as to measure their comprehensions.